Psychosocial working conditions, perceived patient safety and their association in emergency medical services workers in Germany – a cross-sectional study - Antonia Elsässer; Annegret Dreher; Reinhard Pietrowsky; Frank Flake; Adrian Loerbroks (BMC Emergency Medicine, 2024)
Abstract Background Emergency medical service (EMS) workers face challenging working conditions that are characterized by high stress and a susceptibility to making errors. The objectives of the present study were (a) to characterize the psychosocial working conditions of EMS workers, (b) to describe the perceived quality of patient care they provide and patient safety, and (c) to investigate for the first time among EMS workers associations of psychosocial working conditions with the quality of patient care and patient safety. Methods For this cross-sectional study, we carried out an online survey among 393 EMS workers who were members of a professional organization. Working conditions were measured by the Demand-Control-SupportQuestionnaire (DCSQ) and seven self-devised items covering key stressors. Participants reported how often they perceived work stress to affect the patient care they provided and we inquired to what extent they are concerned to have made a major medical error in the last three months. Additionally, we used parts of the Emergency Medical Services – Safety Inventory (EMS-SI) to assess various specific errors and adverse events. We ran descriptive analyses (objective a and b) and multivariable logistic regression (objective c). Results The most common stressors identified were communication problems (reported by 76.3%), legal insecurity (69.5%), and switching of colleagues (48.9%) or workplaces (44.5%). Overall, 74.0% reported at least one negative safety outcome based on the EMS-SI. Concerns to have made an important error and the perception that patient care is impaired by work stress and were also frequent (17.8% and 12.7%, respectively). Most psychosocial working conditions were associated with the perception that patient care is impaired due to work stress. Conclusions Work stress in EMS staff is pronounced and negative safety outcomes or potential errors are perceived to occur frequently. Poor psychosocial working conditions were only consistently associated with perceived impairment of patient care due to work stress. It seems necessary to reduce communication problems and to optimize working processes especially at interfaces between emergency services and other institutions. Legal insecurity could be reduced by clarifying and defining responsibilities. Communication and familiarity between team colleagues could be fostered by more consistent composition of squads.